Increasing the Potential of Tourism Destinations Through Combining the Principles of Sustainability and Innovation - Aziza Ismatillaevna, Fayzieva; Dian Sua Pratama, Bayu; Elya Rohimi, Upit (Journal of World Science, 2023)
The COVID-19 pandemic has had a significant impact on the tourism industry worldwide. Many countries are experiencing significant declines in tourist numbers and tourism revenues. The purpose of this study is to analyze the increase in the potential of tourism destinations through the combination of sustainable principles and innovation. This research is qualitative research carried out using the literature review method by searching for secondary information from various websites that are searched via the internet. In order to increase the potential of tourism destinations through combining the principles of sustainability and innovation, it is important to consider and promote environmental and social sustainability, as well as preserving local cultural heritage. This can help create tourism that is sustainable and profitable for all parties involved, including local communities, tourists, and the environment. Combining the principles of sustainability and innovation can increase the potential of tourism destinations. This research has the implication that by considering sustainable and innovative aspects in the development of tourist destinations, this research provides insight into how the application of sustainable principles and innovation can increase the attractiveness, sustainability, and success of tourist destinations.